A critical review of the vaginal microbiota and its relationship with human papillomavirus - Said Abdallah, Chaharzad; Xu, Tianmin; Wang, Cong (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The study of bacterial 16S rRNA genes is facilitated with the assistance of next-generation sequencing methods (NGS) which allow a thorough investigation of vaginal microbial community makeup to an extent not achievable with regular culture-supported microbiological methods. The human papillomavirus (HPV) triggers cervical intraepithelial neoplasia (CIN), the precursor of cervical malignancy. Vaginal microbiota has a mutualistic symbiotic connection with their host and has a significant influence on health and disease. Surging proof points to a likely connection between the vaginal microbiota and repeated HPV infections. Some vaginal microbial types can be either prophylactic or pathogenic in cancer development of the cervix after repeated HPV infection. In this review, we discussed the composition and structure of the vaginal microbiota as well as the relationship between HPV infection and the vaginal microbiota. We also covered the link between the vaginal microbiome, HPV, and immune response.